A study on mechanical properties of 1H-type crystalline nickel ditelluride - Nguyen Danh Truong; Nguyen Van Quynh (Vietnam Journal of Science and Technology, 2023)
We used the molecular dynamic finite element method with Stillinger-Weber potential to study the mechanical behavior of monolayer 1H-type nickel ditelluride (1H-NiTe2) sheets under uniaxial tension. As the size of the pristine 1H-NiTe2 sheet increases, the Young’s modulus in the armchair direction increases by 6.2 %, while that in the zigzag one decreases by 6.0 %. Both tend to be size-independent in larger sheets and approach the same value at around 54 N/m. The ultimate stress in the armchair direction remains almost unchanged but that in the zigzag one reduces by about 9.5 % as the size inclines. Besides the influence of size, our results show that single vacancy defects strongly affect the ultimate stress and strain while having no effect on Young’s modulus and Poisson’s ratio. When a Te atom is missing at the sheet’s center, the ultimate stress in the armchair direction is reduced by 11.7 %, while a decrease of 16.0 % is caused by a Ni atom vacancy